A Clinical Review on Basic Management of War Injuries / Mass Casualties - Hannan, Md Abdul; Siddiq, AKM Zafrullah; Deb, Anjan Kumar; Maruf, Abdullah Al (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Managing war injury is no longer the exclusive preserve of military surgeons. Increasing numbers of non-combatants are injured in modern conflicts, and peacetime surgical facilities and expertise may not be available. Although all resources are not always available, adherence to the basic management principles following ATLS guideline, can be made in injured patient care in any situation ranging from single person "Buddy" first aid through to major hospital multiple member trauma teams. This article addresses the management of war wounds including mass casualties by non-specialist surgeons with limited resources and expertise. The Initial measures for treating war casualties are similar to those for any severe injury. The warfare Injured patient management is performed into the following levels: a .Management at the site of incident. b. Management en-route to the hospital. c. Hospital management. The primary objectives of injury patient management are: 1. Rapid and accurate assessment of the patients' condition. 2. Resuscitation and stabilization. 3. Ensuring a smooth and rapid hospital transfer. Management is divided into four phases: a. Primary survey b. Resuscitation. c. Secondary survey and d. Definitive care. These proceed sequentially, with the exception that the primary survey and resuscitation should be started at the site of incident & usually proceed simultaneously, with life threatening situations being managed as soon as they are found. A repeat of the secondary survey (Tertiary survey) may also be performed 24 hours later. DOI: 10.3329/jbcps.v27i1.4241 J Bangladesh Coll Phys Surg 2009; 27: 30-38